2019
DOI: 10.1111/dmcn.14264
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of proficiency in powered mobility of children and young adults with motor impairments

Abstract: Aim To identify variables that can predict proficiency in powered mobility use for children in young adults. Method Participants included 80 children and young adults (42 males, 38 females; mean age 10y 2mo, [SD 5y 1mo]; range: 2–22y) with cerebral palsy, neuromuscular disease, and spinal cord injury who participated in the ALYN Hospital Powered Mobility Lending Program from 2009 to 2016. Data were collected and compared before and after participation in the program and powered mobility levels were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results of the primary outcome measure highlight the connection between abilities (GMFCS, MACS, and CFCS) and powered mobility skills (PMP at T3). This is in line with studies that have shown that infants, children, and adults with better manual and communication abilities (such as the ability to stop on demand) also show higher-powered mobility skills (Gefen et al, 2019b;Mockler et al, 2017;Smith et al, 2020). The current study did not find a connection between visual ability and powered mobility skills, which is not in line with Massengale et al (2005).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the primary outcome measure highlight the connection between abilities (GMFCS, MACS, and CFCS) and powered mobility skills (PMP at T3). This is in line with studies that have shown that infants, children, and adults with better manual and communication abilities (such as the ability to stop on demand) also show higher-powered mobility skills (Gefen et al, 2019b;Mockler et al, 2017;Smith et al, 2020). The current study did not find a connection between visual ability and powered mobility skills, which is not in line with Massengale et al (2005).…”
Section: Discussionsupporting
confidence: 86%
“…The pattern of comorbidities that interfere with the ability to learn powered mobility is also true for hand function. Predictive models show that children with limited manual abilities have difficulty mastering driving proficiency, especially those with difficulty controlling a joystick and/or propelling a manual wheelchair for short distances (Gefen et al, 2019b;Mockler et al, 2017). Children at GMFCS levels IV and V often have lower manual abilities as measured by the manual ability classification scale (MACS) (a five-level scale, in which levels three to five imply a consistent reduction of functional abilities (Eliasson et al, 2006); a study showed that 91% of children at GMFCS levels IV and V were at MACS III-V (Carnahan et al, 2007).…”
mentioning
confidence: 99%
“…However, the evidence was mainly based on case studies where the selection process of study participants impacted the risk of potential bias. 36,40,41 Thus, although a joystick steering system has been linked to a higher chance in reaching driving proficiency, 78,79 it is crucial that the chosen steering system fits the potential capabilities and needs of the wheelchair user. For example, for a child with severe CP and very limited manual abilities, alternative head and foot steering systems may well be the only option for independent mobility.…”
Section: Discussionmentioning
confidence: 99%